Is Crocin a Potential Anti-tumor Candidate Targeting Microtubules? Computational Insights From Molecular Docking and Dynamics Simulations - Wang, Ze; Ren, Juan; Jin, Nengzhi; Liu, Xingyi; Li, Xiaofei (Frontiers in Molecular Biosciences, 2020)
Although it is known crocin, a hydrophilic compound from the herbal plant Crocus sativus L., has promising antitumor activity, the detailed mechanism of its antitumor activity was not well understood. Recent experiments suggested tubulin as the primary target for the antitumor activity of crocin. However, due to a lack of crystal structure of tubulin bound with crocin, the exact binding mode and interaction between crocin and tubulin remains exclusive. In the present work, a computational study by integrating multiple conformation docking, molecular dynamics simulation as well as residue interaction network analysis was performed to investigate the molecular mechanism of crocin-tubulin interaction. By comparing the docking score, the most likely binding mode CRO_E1 were identified from twenty different binding modes of crocin in the vinca binding pockets. Further molecular dynamics simulation of CRO_E1 complex showed the binding of crocin is more stable than the inhibitor soblidotin and vinblastine. During the simulation course, an excessive number of hydrogen bonds were observed for the ligand crocin. The binding free energy of crocin-tubulin complex was calculated as -79.25 ± 7.24 kcal/mol, which is almost twice of the ligand soblidotin and vinblastine. By using energy decomposition, hot residues for CRO_E1 were identified as Gln11, Gln15, Thr72, Ser75, Pro173-Lys174-Val175-Ser176-Asp 177, Tyr222 and Asn226 in the β-chain, and Asp245, Ala247-Leu248, Val250, Asn329 and Ile332 in the α-chain. Residue interaction network analysis also showed the importance of these hot residues in the interaction network of crocin-tubulin complex. In addition, a common residue motif Val175-Xxx176-Asp177 was discovered for all three bindings, suggesting its importance in future drug design. The study could provide valuable insights into the interaction between crocin and tubulin, and give suggestive clues for further experimental studies.